Quantitative MRI and Clinical Assessment of Muscle Function in Adults With Cerebral Palsy - Svane, Christian; Forman, Christian Riis; Rasul, Aqella; Nielsen, Christian Hammer; Nielsen, Jens Bo; Lorentzen, Jakob (Frontiers in Neurology, 2021)
Aim: To relate quantitative magnetic resonance imaging (MRI) of ankle plantar flexor muscles to clinical functional tests in adults with cerebral palsy (CP) and neurologically intact (NI) adults. Methods: Eleven adults with CP (aged 41±12, GMFCS level I-II) and eleven NI adults (aged 35±10) participated in this case-control study. We used MRI to assess muscle volume and composition of the triceps surae muscles. We quantified muscle function as maximal voluntary plantarflexion (MVC) torque and countermovement jump (CMJ) height. Results: Compared to NI adults, the MRI intramuscular fat fraction estimate was significantly higher and MRI muscle volume and functional abilities (MVC and CMJ) significantly lower in adults with CP. In NI adults, but not adults with CP, MRI muscle volume correlated significantly with MVC and CMJ. In adults with CP, the estimate of intramuscular fat levels correlated significantly with jump height in a CMJ. Discussion: This study shows reduced muscle volume and altered muscle composition in adults with CP. Muscle composition appears to provide a better marker than muscle volume of reduced muscle function and impaired performance in this population. Measurements of muscle composition could be used in the assessment of neuromuscular impairments and in the determination of rehabilitation protocols in individuals with neurological disorders.